Psychometric properties of the Iranian version of the thirst distress scale and dietary sodium restriction questionnaire for the elderly with heart failure - Khatereh Aminin; Fatemeh Ghaffari; Ali Pourhabib; Zahra Fotokian; Mohammad hassan Nadimi (Babol University of Medical Sciences, 2024)
Background: Recognizing thirst distress and sodium intake restriction using valid and reliable tools enable evidence-based care, and improve treatment outcomes for the elderly with heart failure (HF). The present study investigated the psychometric properties of the thirst distress scale (TDS-HF) and dietary sodium restriction questionnaire for Iranian's elderly with HF (DSRQ-HF). Methods: This crossectional study was conducted during 2021-2022. Two hundred and forty elderly people referring to the cardiology clinics and offices in the western region of Mazandaran, Iran were selected by the convenient sampling method. First, the two questionnaires were translated. Then, face, content, and construct validity were assessed. Several indices were used to evaluate, including the chi-square/degree-of-freedom ratio (CMIN/DF), parsimonious normed fit index (PNFI), comparative fit index (CFI), parsimonious comparative fit index (PCFI). Results: The value of content validity index of all items of the two questionnaires was higher than 0.62. The fit indices, including PCFI=0.594, PNFI=0.582, CMIN/DF=1.987, and CFI=0.979, confirmed the one-factor construct of TDS. PCFI=0.724, PNFI=0.661, CMIN/DF=1.935, ad CFI=0.905, indicated the confirmation of the three-factor construct of DSRQ. The value of Cronbach's alpha of the two questionnaires were 0.86. The value of Ω of the TDS-HF and DSRQ-HF were 0.858, and 0.860, respectively. The value of θ of the TDS-HF and DSRQ-HF were 0.858, and 0.861, representing the suitability of both constructs. Conclusion: The TDS-HF and DSRQ-HF can be used to measure the psychometric effects of diet therapy and behaviors of the elderly with HF in relation to adherence to diet therapy.